The future of comparative immunology - Du Pasquier, Louis (Developmental and comparative immunology, 2024)
« Prediction is very difficult, especially if it is about the future of comparative immunology” could one say to paraphrase Niels Bohr. Yet, if one avoids mistakes of the past and fashions, if one remains ready to welcome surprises an do not to get drowned in big data while profiting from new technologies, if one keeps common sense between expanding and restricting one's scope of investigation in front of the enormous diversity of the tree of life, comparative immunologists are going, in new areas of research and with new tools, to keep contributing enormously to immunology. They will reveal, with the eyes open to homologies and analogies among multiple species, more variations on the theme of immunity and will put the human immune system in perspective a necessary situation to face the questions that remain to be answered in order to improve health or to understand evolution of immune systems. There will always be room in comparative immunology for fundamental approaches to these subjects. A proper education, aimed at combining competences, will be essential to achieve these goals. •Comparisons: a necessity in immunology, like in any domain, now and in the future.•Remaining open to future surprises. Avoid the danger of mindsets and fashions.•Education necessary in the future to explain the above points to non specialists.